Cured - Grinnell, Dustin (Ars Medica, 2024)
Italian for “bad air,” malaria has been a persistent threat to humans for over 4,000 years. Since the first infected human, scientists have searched for a drug to beat the global killer. In Cured, Peter Spaulding, a disillusioned doctoral student from Harvard, has been trying to develop a malaria drug for years.